Prolonged Slow Expiration Technique and Gastroesophageal Reflux in Infants Under the Age of 1 Year - Lievens, Laure; Vandenplas, Yvan; Vanlaethem, Sylvie; Van Ginderdeuren, Filip (Frontiers in Pediatrics, 2021)
Background: The Prolonged Slow Expiration Technique (PSE) is an airway clearance technique (ACT) carried out in newborn children with bronchial obstruction and hypersecretion to clear away the mucus from the respiratory tract. Evidence about the effect of PSE on gastroesophageal reflux (GER) is currently lacking in the literature. This study aimed to evaluate the influence of PSE on GER in infants under the age of 1 year. Methods: Infants were observed using multichannel intraluminal impedance-pH monitoring (MII-pH) over 24 h. During monitoring, the participants were treated with one 20 min intervention of PSE in supine position, 2 h after feeding. In this controlled trial with intra-subject design, the number of reflux episodes (REs) during PSE were compared to 20 min before and after PSE. Results: Fifty infants younger than 1 year were screened of whom 22 had a pathological GER. For the entire group, no significant difference was seen in the total number of REs between before, during, or after the PSE treatment (P = 0.76). No significant difference in total REs was found between the three measuring points (P = 0.59) in the group of infants with an abnormal MII-pH (n = 22). Conclusion: PSE does not cause a significant difference in REs in infants younger than 1 year. Registration number: NCT03341585.